Macroglossia in Beckwith-Wiedemann Syndrome: A Narrative Review - Dwi Ariani; Pindobilowo (Formosa Journal of Applied Sciences, 2023)
Beckwith-Wiedemann syndrome has a wide spectrum of clinical features, namely macroglossia, defects in the abdominal wall and an increased risk of developing embryonal tumors during childhood. Macroglossia can cause several disorders such as airway obstruction, dysphagia, drooling, speech difficulties and other disorders. To determine the etiology and clinical picture and to differentiate macroglossia in BWS from macroglossia in other diseases so as to be able to make a diagnosis and plan the right treatment. Collecting and analyzing relevant references in the form of journals and textbooks accessed through the Google Scholar, Google Books, PubMed and Science Direct databases. Macroglossia in BWS and macroglossia in other diseases can be distinguished if an appropriate diagnosis is made by means of a complete clinical and physical examination so that clinical symptoms and possible etiological factors can be identified.